The Effect Of Sustainable Commitment And Sustainable Competencies On Business Sustainability - Ardika Sulaeman; Susanti Susanti Kurniawati (Jurnal Economia, 2023)
AbstractThis research is motivated by the low business sustainability of MSMEs in West Java. In MSMEs, human resources play an important role in the development of MSME businesses. This study aims to determine the effect of sustainable commitment and competencies on the business sustainability of MSMEs. This research was conducted using a quantitative approach with a survey method of 209 fish processing business owners in West Java. Data collection was carried out by survey using a questionnaire instrument. Data analysis was performed with AMOS SEM. The results of this study reveal that the best business sustainability is in the social sustainability dimension and the lowest is economic sustainability. Sustainable commitment is mainly shown by a high commitment to reduce energy use, while sustainable competencies are shown by a better ability to motivate workers and collaborate with similar businesses. In addition, sustainable commitments and sustainable competencies affect business sustainability.Keywords: Business, Sustainability, Competencies, Commitment, Green